2015
DOI: 10.1371/journal.pone.0119857
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of Cell Metabolic Pathways and Oxidative Stress Signaling Contribute to Acquired Melphalan Resistance in Multiple Myeloma Cells

Abstract: Alkylating agents are widely used chemotherapeutics in the treatment of many cancers, including leukemia, lymphoma, multiple myeloma, sarcoma, lung, breast and ovarian cancer. Melphalan is the most commonly used chemotherapeutic agent against multiple myeloma. However, despite a 70–80% initial response rate, virtually all patients eventually relapse due to the emergence of drug-resistant tumour cells. By using global proteomic and transcriptomic profiling on melphalan sensitive and resistant RPMI8226 cell line… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
54
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(57 citation statements)
references
References 77 publications
3
54
0
Order By: Relevance
“…The inhibition of Warburg effect deprives the generation of ATP, decreasing cancer cells growth and proliferation [10, 11]. Thus, Warburg effect has received substantial attention as a novel therapeutic target in cancers including lung cancer [12, 13], leukemia [14], breast cancer [1518], pancreatic cancer [19, 20], colorectal cancer [21, 22], bladder cancer [23], and multiple myeloma [24, 25]. In multiple myeloma, dichloroacetate, which is an inhibitor of aerobic glycolysis, has been reported to increase myeloma cell sensitivity to bortezomib [24].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The inhibition of Warburg effect deprives the generation of ATP, decreasing cancer cells growth and proliferation [10, 11]. Thus, Warburg effect has received substantial attention as a novel therapeutic target in cancers including lung cancer [12, 13], leukemia [14], breast cancer [1518], pancreatic cancer [19, 20], colorectal cancer [21, 22], bladder cancer [23], and multiple myeloma [24, 25]. In multiple myeloma, dichloroacetate, which is an inhibitor of aerobic glycolysis, has been reported to increase myeloma cell sensitivity to bortezomib [24].…”
Section: Introductionmentioning
confidence: 99%
“…In multiple myeloma, dichloroacetate, which is an inhibitor of aerobic glycolysis, has been reported to increase myeloma cell sensitivity to bortezomib [24]. Additionally, inhibition of aerobic glycolysis was found to contribute to melphalan treatment in myeloma [25]. Pyruvate kinase (PK) is one of the key regulators of the Warburg effect that convert phosphoenolpyruvate (PEP) to pyruvate and generate one molecular of ATP [26, 27].…”
Section: Introductionmentioning
confidence: 99%
“…124126 Using transcriptomic and proteomic approaches, Zub et al observed that in melphalan-resistant myeloma cell lines, there is a metabolic switch conforming to the Warburg effect (aerobic glycolysis) and an elevated oxidative stress response, resulting in enhanced survival and proliferation partially mediated by VEGF/IL-8 signaling. 127 Specifically, in melphalan-resistant myeloma cell line RPMI8226, most of the glycolytic and pentose phosphate–pathway enzymes were upregulated, whereas the tricarboxylic acid cycle and electron transport chain proteins were downregulated. The switch of metabolic dependence to aerobic glycolysis implicates the glycolytic pathway as a potential target for therapeutic intervention to improve the efficacy of chemotherapy.…”
Section: Cancer Cells Adapt Metabolically In Response To Chemothementioning
confidence: 99%
“…Several studies have demonstrated a link between altered cell metabolism and the development of multidrug resistance in multiple cancer types [114][115][116] , including prostate [117] . Prostate cancer progression is a complex process.…”
Section: Exosome-regulated Metabolism and Drug Resistancementioning
confidence: 99%